2012
DOI: 10.1155/2012/463617
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MAPK in Drug-Induced Kidney Injury

Abstract: This paper focuses on the role that mitogen-activated protein kinases (MAPKs) play in drug-induced kidney injury. The MAPKs, of which there are four major classes (ERK, p38, JNK, and ERK5/BMK), are signalling cascades which have been found to be broadly conserved across a wide variety of organisms. MAPKs allow effective transmission of information from the cell surface to the cytosolic or nuclear compartments. Cross talk between the MAPKs themselves and with other signalling pathways allows the cell to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 132 publications
1
40
0
4
Order By: Relevance
“…These findings are in harmony with the reported CM suppression of MAPKs pathway in Adjuvant arthritis [13] and LPS-induced respiratory distress [47] along with abrogation of NF-κB signaling in wounds of diabetic rats [18]. Interestingly, blockade of MAPKs signaling, in particular, p38 and JNK pathways, has been shown to protect against acute renal failure, tubular cell apoptosis and histopathological damage in multiple renal injury models [5, 48]. The observed CM inhibition of MAPKs pathway together with downstream effectors including NF-κB and inflammatory cytokines has been regarded as an effective strategy for the management of diverse renal injuries [4, 6].…”
Section: Discussionsupporting
confidence: 80%
“…These findings are in harmony with the reported CM suppression of MAPKs pathway in Adjuvant arthritis [13] and LPS-induced respiratory distress [47] along with abrogation of NF-κB signaling in wounds of diabetic rats [18]. Interestingly, blockade of MAPKs signaling, in particular, p38 and JNK pathways, has been shown to protect against acute renal failure, tubular cell apoptosis and histopathological damage in multiple renal injury models [5, 48]. The observed CM inhibition of MAPKs pathway together with downstream effectors including NF-κB and inflammatory cytokines has been regarded as an effective strategy for the management of diverse renal injuries [4, 6].…”
Section: Discussionsupporting
confidence: 80%
“…AmB-treated kidney cells also exhibited acute increments in the sphingomyelin-phosphatidylcholine molar ratios and ceramide content, supporting the idea of the involvement of lipid raft signaling components in AmB toxic action (84). In this regard, there is increasing evidence that activation of MAPKs, which are kinases known to show cross talk with Ras and other signaling pathways, plays an important role in drug-induced kidney injury (85).…”
Section: The Development Of Amb Toxicity and Resistance In Cholesteromentioning
confidence: 71%
“…Activation of ERK is mainly associated with growth promotion, oxidative stress and inflammatory process [23]. In addition, ERK signaling plays an important role in mediating renal cell responses to a diverse range of stimuli and has previously been shown to be involved in compensatory renal hypertrophy and glomerular and tubulointerstitial diseases [24]. Furthermore, previous study demonstrated that, the ERK signaling pathway is activated in polycystic kidney disease and inhibitors of this pathway reduce renal inflammation and improve renal function [24].…”
Section: Discussionmentioning
confidence: 99%